2012
DOI: 10.5688/ajpe768156
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Mission to Guatemala as an Advanced Pharmacy Practice Experience

Abstract: Objective. To describe the development and outcomes of an advanced pharmacy practice experience (APPE) for a medical mission trip to Guatemala. Design. Pre-mission preparation and post-mission reflection activities were combined with in-country activities to create a 5-week APPE. During the 10-day medical mission trip, pharmacy students dispensed medications, counseled patients, conducted quality improvement assessments, and presented their findings and experiences as part of an interdisciplinary health care t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…[25][26][27] Additionally, the option of a required IPPE/ APPE may provide further opportunities to enhance cultural competency. [22][23][24][25][26][27] Students' mean scores at baseline were close to the ideal responses (ie, strongly agree51) for the cultural empathy statements and 1 of the cultural skills statements about avoiding rumors, opinions, comments, or any other factors that may negatively impact the cultural encounter. There are several possible reasons for these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] Additionally, the option of a required IPPE/ APPE may provide further opportunities to enhance cultural competency. [22][23][24][25][26][27] Students' mean scores at baseline were close to the ideal responses (ie, strongly agree51) for the cultural empathy statements and 1 of the cultural skills statements about avoiding rumors, opinions, comments, or any other factors that may negatively impact the cultural encounter. There are several possible reasons for these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some institutions have described and evaluated culturally relevant activities, such as lectures, case-based assessments, simulated and/or standardized patient activities; guest lecturers from various cultural, racial, ethnic, socioeconomic, and spiritual backgrounds; and other active-learning techniques. [16][17][18][19][20][21][22][23][24][25][26][27] Activities such as these could be threaded throughout the degree program. [25][26][27] Additionally, the option of a required IPPE/ APPE may provide further opportunities to enhance cultural competency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some US pharmacy schools have tried to include a medical mission as an advanced pharmacy practice experience (APPE) or an elective course in their pharmacy curricula. [7][8][9] The students who participated in the medical mission APPE reported that this type of APPE provided the opportunities regarding interdisciplinary education, cultural competence, and patientfocused care which should be addressed in APPE. 8 Some studies have also introduced how to prepare a pharmacyled medical mission trip.…”
Section: Introductionmentioning
confidence: 99%
“…1 Around and since that time, articles reinforcing the importance of exposing students to experiences that hone cultural competency have appeared in print. [2][3][4][5][6][7][8][9] Examples of the centrality of cultural competency to contemporary practice include the ongoing work of the American Association of Colleges of Pharmacy (AACP) Caring for the Underserved Curriculum Task Force, the inclusion of cultural sensitivity in the Approach to Practice and Care domain of the 2013 CAPE Educational Outcomes, and cultural awareness and sensitivity elements within Standards 3, 25, and Appendices 1-3 of the draft ACPE Standards 2016. [10][11][12] However, a review of the literature indicates that, while some programs incorporate a brief immersion into their cultural enrichment experiences, the elective courses in Native American cultures and health are relatively unique with respect to their emphasis on career discernment within the studied population.…”
Section: Introductionmentioning
confidence: 99%